Role of parental smoking in severe bronchiolitis: a hospital based case-control study - K., Mohamad Ismael; Jose, Santhosh (International Journal of Contemporary Pediatrics, 2017)
Background: Bronchiolitis is one of the commonest causes of hospitalization of infants and young children in India. Parental smoking is an important risk factor for both susceptibility and severity of bronchiolitis. Paternal smoking alone causes a 1.3-fold (95% CI = 1.2-1.4) increase in risk. The aim of this study was to find out the role of parental smoking in severe bronchiolitis. Methods: This is a case control study conducted in the Department of Pediatrics from July 2013 to December 2015. Sixty-four patients admitted into the ward with severe bronchiolitis were enrolled as cases and sixty-four suitably matched apparently healthy children attending EPI centre and outpatient department presenting with non-respiratory illness were enrolled as controls. Every second case satisfying the inclusion and exclusion criteria was enrolled in the study. Results: The mean age of the patients was 8.53 (SD±4.75) months. Forty-two (65%) patients were male and twenty-two (34.3%) patients were female. Male-to-female ratio was 1.9:1. Most of the cases (62.5%) came from low socioeconomic background. More than half of the cases (53.13%) were not exclusively breastfed babies. Mean length of hospital stay was SD (5.41±2.82) days. Thirty-nine (60%) cases and twenty-three (35%) controls were exposed to parental smoking. Result was highly significant (p = 0.005). Odds ratio was 2.8 (95% CI from 1.36 to 5.68). Conclusion: Exposure to parental smoking causes a statistically significant (p = 0.005, odds ratio = 2.8) increase in the risk of developing severe bronchiolitis in the first year of life